Time constraints on Early Tonian Rifting and Cryogenian Arc terrane-continent convergence along the northern margin of the West African craton: Insights from SHRIMP and LA-ICP-MS zircon geochronology in the Pan-African Anti-Atlas belt (Morocco) - Bouougri, El Hafid; Lahna, Abdelhak Ait; Tassinari, Colombo C.G.; Basei, Miguel A.S.; Youbi, Nasrrddine; Admou, Hassan; Saquaque, Ali; Boumehdi, Moulay Ahmed; Maacha, Lhou (Gondwana research, 2020)
The Neoproterozoic Anti-Atlas belt (Morocco) is a key segment in tracing the history of the northern margin of the West African craton (WAC) from Rodinia breakup to Gondwana assembly. In order to constrain geodynamic events related to rifting and convergence and their stratigraphic records, a radiometric study was carried out on the volcano-sedimentary Tachdamt and Bleïda Formations. The volcaniclastic deposits of Tachdamt Fm. yield an age of ca. 883 Ma and provide a new constraint for the timing of the subaqueous volcanic eruption and the initiation of rifting in the Anti-Atlas. This age is ~100 my older than the previous age of 788 ± 10 Ma obtained from Rb/Sr isotope dating (Clauer, 1976). Available zircon data from the interbedded clastic deposits from Tachdamt Fm. indicate major shifts in provenance during the rifting with sediments sourced from the WAC and a nearby Grenvillian terrane. Detrital zircon ages from metasiltstones of Bleïda Fm. set a maximum depositional age at ca. 700 Ma. The age spectra discloses a major shift in sediment input with provenance from the WAC, Grenvillian terrane and an arc-related terrane (ca. 770–700 Ma) lying along the Anti-Atlas margin. The newly obtained results combined with existing radiometric data allowed the refinement of the stratigraphic and geotectonic framework of the pre-Pan-African strata in the WAC. The Early Tonian syn-rift volcanism has much in common with similar events in other cratons and provides a stratigraphic record for incipient Rodinia breakup. The overlying Bleïda Fm. deposited in a peripheral foreland basin chronicles the Cryogenian arrival of the ca. 770–700 Ma Bou Azzer-Siroua arc-related terrane at the Anti-Atlas margin, and correlates with initial accretion in West Gondwana. The new results indicate that the Grenvillian detrital input in the Anti-Atlas during both geodynamic stages points toward a possible Mesoproterozoic terrane existing along the western margin of the WAC. [Display omitted] •We present U-Pb dating of Early Tonian rifting and related volcanism of the Tachdamt Fm. in the Anti-Atlas belt.•U-Pb dating detrital zircon grains of Bleïda Fm. provides a maximum depositional age of ca. 700 Ma.•The Bleïda Fm. chronicles arrival of arc-related terrain at the cratonic margin of Anti-Atlas during the Cryogenian.•Both Formations record major shifts in provenance, with evidences for zircon grains sourced from a Grenvillian terrane.•Both Formations correlate respectively with early Rodinia Breakup and initial accretion at north Gondwana margin.